First report and pathogenicity of Myrothecium roridum, Curvularia eragrostidis and C.lunata on seeds of Striga hermonthica in Nigeria - Czerwenka-Wenkstetten, I.M.; Berner, D.K.; Schilder, A.; Gretzmacher, R. (Scientific Societies, 1997)
Striga is a weed known to be devastating to crops in the tropics. Yield reductions in maize of up to 90% have been observed in West Africa. In September 1994, a seed lot of Striga hermonthica (harvested in 1993 in sorghum fields in Abuja, Nigeria) was observed to have a very low germination rate (20 to 40%). Single-spore isolates from fungal colonies growing on the striga seeds were identified as Myrothecium roridum, Curvularia eragrostidis, and C. lunata. Pathogenicity to striga was tested. Striga seeds were preconditioned for 10 days at 28°C in darkness to break dormancy, then surface sterilized in 1% NaOCl for 7 min, rinsed in sterile, distilled water, and placed in eight central wells of a 24-well plate with up to 300 seeds per well. Seeds were covered with water and inoculated with fungi by placing in each well a 4-mm-diameter hyphal plug taken from a 4-day-old potato dextrose agar culture of one of the isolates. Seeds without fungi served as controls. After 24 h, striga seeds were surface sterilized as above and dispersed evenly in petri dishes with two layers of filter paper soaked in 10 ppm of 1,000 ml of GR-24 (3 [2,5-Dihydro-3-methyl-2-oxo-5-furanyl) oxymethylene]-3, 3a, 4, 8b-tetra-hydroindeno-[1, 2-b] furan-2-one) to induce germination. Seed germination was evaluated after 24 h of incubation in darkness at 33°C. Striga germination was reduced by 100% by M. roridumand 48% by C. era-grostidis and C. lunata.